2011
DOI: 10.3747/pdi.2009.00171
|View full text |Cite
|
Sign up to set email alerts
|

Early Initiation of Continuous Ambulatory Peritoneal Dialysis in Patients Undergoing Surgical Implantation of Tenckhoff Catheters

Abstract: Early initiation of CAPD with surgically implanted Tenckhoff catheters is feasible and safe. Shorter break-in periods are not associated with more catheter-related complications. The data from our peritoneal dialysis population suggest that early initiation is not associated with an increased number of complications. This needs to be confirmed in a randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
101
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 19 publications
13
101
1
5
Order By: Relevance
“…In a recent retrospective study, 226 patients who started CAPD ≤ 14 days after implantation were compared to 84 patients starting CAPD>14 days after implantation. Catheter-related complications within 6 months were no different between early and late groups (14.6 vs. 13.1% respectively) [11].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In a recent retrospective study, 226 patients who started CAPD ≤ 14 days after implantation were compared to 84 patients starting CAPD>14 days after implantation. Catheter-related complications within 6 months were no different between early and late groups (14.6 vs. 13.1% respectively) [11].…”
Section: Discussionmentioning
confidence: 88%
“…The authors of all the mentioned reports [3,9,11,[16][17][18][19][20] showed that a shortened break-in period for initiating the utilization of a TC is feasible and safe. However, the studies have substantial differences in their design and results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations